Analysis of The Level of Professionalism and Career Development of Accounting Department Alumni in State University - Idris, Hariany; Anwar, Samsinar; Syachbrani, Warka; Dunakhir, Samirah (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This research aims to analyze the knowledge and understanding of points of view in selecting quality levels for students majoring in accounting at state universities. This research is quantitative research with the unit of analysis being Alumni of the Department of Accounting, Faculty of Economics and Business, Makassar State University. The research was carried out for three months, starting from collecting existing data to direct observation in the field. This research produced interesting findings, including that the majority of alumni wanted to work in the government sector, but in reality the majority worked as private employees. Regarding the suitability of the field of science, alumni generally work in accordance with the field they studied and the major they took during their education. Furthermore, this research also obtained alumni’s ideas for improving field work practices in companies/government agencies as well as English language skills, computer skills and department-specific practices.